Examination of the Role of Corporate Branding in Achieving Business Excellence Requirements in Agencies of Algerian Companies - Derroum, Ahmed; Haouati, Ouarda (Economics and Business, 2021)
This study seeks to define the role of corporate brands in achieving business excellence by conducting a field study on the agencies of Algerian mobile operators “Mobilis” and “Djezzy” in the state of Djelfa where the questionnaire has been used for the collection of opinions sample (45 employees) and then processed with the statistical program (SPSS). The results have shown that there is high awareness of corporate brands and business excellence. We have also found that the two dimensions of corporate brand (strategic vision, stakeholder image) affect the business excellence, whereas the organizational culture does not affect it. The results have also demonstrated that corporate brands as a group explain 47 % of the variation in business excellence, while the difference test have demonstrated that the awareness of the sample about “corporate brands” is not different according to the company but the awareness of the business excellence is in favor of the company “Mobilis” at the expense of the mobile operator “Djezzy”.